Identifikasi Kandidat Target Obat Ulcerative Colitis (UC) Menggunakan Pendekatan Bioinformatika Menuju Precision Medicine - Sianu, Rahman Sumani; Jannah, Miftahul; Mauri, Ariesa; Ayu L, Putri; Yuni N, Eka; Pratiwi G, Annisa (Program Studi S1 Farmasi, STIKES Senior, Medan, 2025)
Ulcerative Colitis (UC) is a chronic inflammation of the lining of the digestive tract, primarily in the rectum and colon. Genetics is a factor in the occurrence of UC. This becomes a challenge in finding new drugs to treat the disease based on certain genes. So, the aim of this research is to identify candidate therapeutic targets in UC. We used the Genomic-Wide Association Studies (GWAS) catalog to collect data on gene variations associated with UC and then identified missense genes as target genes in this study using HaploReg v4.2. The final stage, to determine the pharmacological action of drugs on the target genes, we used Drugbank and the Drug-Gene Interaction database (DGIdb). Our analysis yielded 760 SNPs associated with UC disease. In the next stage, score classification was performed based on six functional annotations including Missense, cis-eQTL, Biological Process, Cellular Component, Molecular Function, and KEGG Molecular Pathway. Based on these annotation criteria, 16 genes with a score ≥2 were identified, namely PRKCQ, TLR4, IFIH1, CARD9, TYK2, CD6, NOD2, PLCG2, SMAD3, FCGR2A, IL-23R, SH2B3, IL-17REL, FUT2, GSDMB, and IL-7R. These genes became biomarkers and drug targets in this study. From the 16 genes, 83 drugs were obtained using the Drugbank and DGIdb databases. However, there are 4 drugs that can be proposed as candidates for the treatment of UC disease, namely tamoxifen (PRKCQ Inhibitor), cyclobenzaprine (TLR4 Inhibitor), benzoyl peroxide (PRKCQ Inhibitor), and pazopanib (SH2B3 Inhibitor). These drugs are candidates for UC therapy because they have not yet been tested either preclinically or clinically for the indication of ulcerative colitis. This genomic analysis significantly aids in identifying genes closely associated with UC and provides insights for defining important targets in new drug discovery. Therefore, further exploration and research related to these drugs are crucial, offering a promising path to advance UC treatment strategies.